2023
DOI: 10.1021/acs.analchem.3c01137
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctionalized Covalent Organic Frameworks for Broad-Spectrum Extraction and Ultrasensitive Analysis of Per- and Polyfluoroalkyl Substances

Abstract: The contamination of surface and ground water by per-and polyfluoroalkyl substances (PFASs) has become a growing concern, and the structural diversity of PFASs is the major challenge for their ubiquitous applications. Strategies for monitoring coexistent anionic, cationic, and zwitterionic PFASs even at trace levels in aquatic environments are urgently demanded for effective pollution control. Herein, novel amide group and perfluoroalkyl chain-functionalized covalent organic frameworks (COFs) named COF-NH-CO-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…COFs as SPME coatings, prepared by physical adhesion, the sol–gel method, in situ growth, and chemical cross-linking, have recently attracted considerable attention for the analysis of organic pollutants, including polycyclic aromatic hydrocarbons [ 94 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ], phenols [ 97 , 113 , 114 , 115 ], polybrominated diphenyl ethers [ 98 , 100 , 116 , 117 , 118 , 119 , 120 ], polyhalogenated biphenyls [ 99 , 121 , 122 ], pesticides [ 123 , 124 , 125 , 126 , 127 , 128 ], and PFASs [ 129 , 130 , 131 ] in environmental samples. The COF-based coatings used for the extraction of targeted compounds in environmental samples are summarized in Table 2 .…”
Section: Covalent Organic Framework (Cofs)mentioning
confidence: 99%
See 2 more Smart Citations
“…COFs as SPME coatings, prepared by physical adhesion, the sol–gel method, in situ growth, and chemical cross-linking, have recently attracted considerable attention for the analysis of organic pollutants, including polycyclic aromatic hydrocarbons [ 94 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ], phenols [ 97 , 113 , 114 , 115 ], polybrominated diphenyl ethers [ 98 , 100 , 116 , 117 , 118 , 119 , 120 ], polyhalogenated biphenyls [ 99 , 121 , 122 ], pesticides [ 123 , 124 , 125 , 126 , 127 , 128 ], and PFASs [ 129 , 130 , 131 ] in environmental samples. The COF-based coatings used for the extraction of targeted compounds in environmental samples are summarized in Table 2 .…”
Section: Covalent Organic Framework (Cofs)mentioning
confidence: 99%
“…The use of COFs as SPME coatings for the extraction of PFASs has been proposed as a valid alternative to the use of MOFs, featuring a highly hydrophobic and π electron-rich structure [ 129 , 130 , 131 ]. In this context, a novel dioxin-linked COF (TH-COF) was synthesized by microwave-promoted nucleophilic substitution of 2,3,5,6-tetrafluoro-4-pyridinecarbonitrile with 2,3,6,7,10,11- hexahydroxy triphenylene [ 129 ].…”
Section: Covalent Organic Framework (Cofs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have shown that adsorbents with cationic groups or fluorocarbon chains ,, interact strongly with the respective components of PFAS adsorbates (Figure a). This strategy has borne fruit in the design of PFAS-selective COFs.…”
Section: Introductionmentioning
confidence: 99%